THE MOBILE ROBOT DEVELOPMENT FOR AIR POLLUTION TELE DATA CAPTURE - Dirman Hanafi; Khairul Azlan A.Rahman (Jurnal Teknologi Elektro, 2016)
In the Modern era, the environmental issues have given significant impact to the human live. The air pollution indoor and outdoor environment sometimes dangerous to the human health and it needs to be justified. To fulfill this purpose, in this research tele-measurement process and technique based on the mobile robot with equipped by several air quality parameters sensors is developed. The robot is controlled using remote control and wireless communication system. The air quality in target area will be monitored by using sensors which will capture data and send it to the Central Control (laptop) for analyzing. And then to be able to monitor the certain area investigation, the mobile robot is guided by using wireless camera. From the experimental test, the robot able move to target area, capture the area condition and the air parameters monitor. Keywords: air pollution, tele-measured, mobile robot